Recombinant human thrombopoietin improved platelet engraftment after autologous hematopoietic stem cell transplantation in patients with newly diagnosed multiple myeloma. (26th September 2021) - Gu, Jingli; Liu, Junru; Li, Xiaozhe; Zou, Waiyi; Huang, Beihui; Chen, Meilan; Li, Juan
Abstract: Background: To evaluate the efficacy and safety of recombinant human thrombopoietin (rhTPO) for hematopoietic reconstitution after autologous stem cell transplant (ASCT) in patients with newly diagnosed multiple myeloma (NDMM). Method: Thirty‐five cases with NDMM had been enrolled into a prospective clinical trial from March 2014. The hematopoietic reconstitution was compared between these 35 cases (rhTPO group) and 98 historic cases not receiving rhTPO (control group) after stem cell reinfusion. Results: Thirty‐five (100%) cases receiving rhTPO achieved both neutrophil and platelet engraftment within 30 days post‐transplant. The median time to neutrophil and platelet engraftment was the 10 th day and 11 th day after stem cell reinfusion, respectively. Multivariate analysis showed that rhTPO administration was an independent factor for accelerating platelet engraftment (HR 2.013, 95% CI 1.336–3.034, p = 0.001). Subgroup analysis showed that rhTPO improved platelet engraftment and alleviated platelet transfusion needs in patients with inadequate re‐infused CD34 + cell counts of <2 × 10 9 /L. All the 35 patients tolerated rhTPO well. Survival analysis showed no decrease in time to progression (TTP) or overall survival (OS) by rhTPO administration. Conclusion: rhTPO accelerated the platelet engraftment after ASCT in patients with NDMM with good tolerability and long‐term safety, especially for those patients with poor CD34 + cell reinfusion. rhTPO might be recommended to be used early after ASCT for patients with NDMM. Abstract : This study aimed to evaluate the efficacy and safety of recombinant human thrombopoietin (rhTPO) for hematopoietic reconstitution after autologous stem cell transplant (ASCT) in patients with newly diagnosed multiple myeloma (NDMM). Multivariate analysis showed that rhTPO administration was an independent factor for accelerating platelet engraftment. Survival analysis showed no decrease on TTP or OS by rhTPO application.